2019
DOI: 10.1590/1981-86372019000493499
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and dental caries of schoolchildren from Sobral - Ceará

Abstract: Objective: To examine the relationship between nutritional status and dental caries of schoolchildren from Sobral, Ceará, Braszil. Methods: Dental health and nutritional status of 92 children studying in two different schools and aging 5 years old were evaluated. The nutritional status was evaluated using the Body Mass Index (BMI), and the dental health status was evaluated using the Decayed, Missing, and Filling Tooth Index (DMFT-index). An interview with the parents of the children was also performed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(16 reference statements)
2
2
0
3
Order By: Relevance
“…In the present study, children who consume carbonated drinks are higher in urban school (74%), and this is in agreement with Chandrasekar et al not agreement with Biria et al 7 and Aguiar et al 8 Risk of caries is high among children consuming soft drinks compared to those who are not. Carbonated drinks contain acids such as phosphoric acid, citric acid, and carbonic acid that destroy the tooth surface causing erosion.…”
Section: Carbonated Drinkssupporting
confidence: 92%
“…In the present study, children who consume carbonated drinks are higher in urban school (74%), and this is in agreement with Chandrasekar et al not agreement with Biria et al 7 and Aguiar et al 8 Risk of caries is high among children consuming soft drinks compared to those who are not. Carbonated drinks contain acids such as phosphoric acid, citric acid, and carbonic acid that destroy the tooth surface causing erosion.…”
Section: Carbonated Drinkssupporting
confidence: 92%
“…Kejadian tersebut ditandai dengan konsentrasi penyakit pada kelompok kecil orang terutama pada mereka yang hidup dalam konteks sosiodemografi yang lebih buruk. Masyarakat berpenghasilan rendah seringkali lebih rentan terhadap karies terutama karena kebiasaan gizi ibu dan anak yang buruk (Aguiar et al, 2019).…”
Section: Pendahuluanunclassified
“…Berdasarkan hasil literature review pada 12 jurnal, telah didapatkan beberapa penyebab mendasar dari status gizi pada status kesehatan gigi anak sekolah, yaitu krisis sosial ekonomi, dan krisis politik (Aluckal et al, 2016;Halder et al, 2018;Dikshit et al, 2018;Jankovic et al, 2018;Aguiar et al, 2019;Goodarzi et al, 2019;Zahid et al, 2020).…”
Section: Penyebab Mendasar Dari Status Gizi Pada Status Kesehatan Gigi Anak Usia Sekolahunclassified
See 1 more Smart Citation
“…While in the past, the focus of studies on dental caries was the relationship between biological and dietary variables in the process of the appearance of dental caries, in the last decades, there has been greater interest in researching how demographic and socioeconomic characteristics play a role in the prevalence of this disease in the population [2]. Worse oral health rates are observed in low-income children [1,3,5,[11][12][13][14][15]. Regarding sociodemographic variables, a statewide study carried out in Minas Gerais found higher dental caries prevalence in 12-year-old children when comparing countryside cities with the state capital [16].…”
Section: Introductionmentioning
confidence: 99%